Surface relaxation and permeability of cement pastes with hydrophobic agent: Combining 1H NMR and BET. (13th December 2021) - Zhang, Hao; Zhao, Haitao; Mu, Song; Cai, Jingshun; Xiang, Yu; Wang, Jiawei; Hong, Jinxiang
Highlights: The effect of hydrophobic agent on surface relaxation and permeability of cementitious materials is assessed experimentally. The change of pore structure and pore surface properties are investigated by BET and NMR method. The analytical Kozeny equation is utilized to predict the permeability of cement pastes with hydrophobic agent. Abstract: The carboxylic acid ammonium salt is mixed into the concrete matrix to resist water with corrosive ions to improve concrete durability. The 1H NMR and BET experimental methods were applied to evaluate the effect of carboxylic acid ammonium salt on pore surface and structure. The results show that the surface relaxation of cement pastes containing hydrophobic agent is reduced to 60% of reference sample and excellent consistency exists between surface relaxation and water adsorption. The analytical Kozeny equation is utilized to predict the permeability of cement pastes containing different amounts of carboxylic acid ammonium salt. Results show that the reduction trend changes with carboxylic acid ammonium salt amount due to the fact that the addition of hydrophobic agent changes the pore structure. It can be concluded that the generation of the flaky crystals results in the change of pore structure and pore surface properties which can increase the water resistance ability of pore in cement paste mixing with hydrophobic agent. These results reveal the mechanism of carboxylic acid ammonium salt integral addition on hydrophobicity of cementitious materials and provide the guidance to improve the hydrophobic agent application properties.